2001
DOI: 10.1074/jbc.m011534200
|View full text |Cite
|
Sign up to set email alerts
|

Telomeric Protein Pin2/TRF1 as an Important ATM Target in Response to Double Strand DNA Breaks

Abstract: ATM mutations are responsible for the genetic disease ataxia-telangiectasia (A-T). ATM encodes a protein kinase that is activated by ionizing radiation-induced double strand DNA breaks. Cells derived from A-T patients show many abnormalities, including accelerated telomere loss and hypersensitivity to ionizing radiation; they enter into mitosis and apoptosis after DNA damage. Pin2 was originally identified as a protein involved in G 2 /M regulation and is almost identical to TRF1, a telomeric protein that nega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
89
0
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(96 citation statements)
references
References 75 publications
6
89
0
1
Order By: Relevance
“…The striking correlation between the appearance of retained ATM and of histone H2AX (?-H2AX), and the rapid association of a fraction of ATM with ?-H2AX foci, are consistent with a major role for ATM in the early detection of DSBs and subsequent induction of cellular responses. It has been reported that ATM protein interacts with TRF1 (Kishi et al, 2001) and lack of TRF2 results in apoptosis in ATM function dependent (Karlseder et al, 1999). These reports further propose the role of ATM in telomere maintenance.…”
Section: Atm De®ciency In¯uences Telomere Chromatin Structuresupporting
confidence: 52%
See 1 more Smart Citation
“…The striking correlation between the appearance of retained ATM and of histone H2AX (?-H2AX), and the rapid association of a fraction of ATM with ?-H2AX foci, are consistent with a major role for ATM in the early detection of DSBs and subsequent induction of cellular responses. It has been reported that ATM protein interacts with TRF1 (Kishi et al, 2001) and lack of TRF2 results in apoptosis in ATM function dependent (Karlseder et al, 1999). These reports further propose the role of ATM in telomere maintenance.…”
Section: Atm De®ciency In¯uences Telomere Chromatin Structuresupporting
confidence: 52%
“…How the absence of ATM in¯uences the association of telomeres with the nuclear matrix is not presently clear. One assumption is that ATM regulates the function of Pin2/TRF1 as activated ATM directly phosphorylated Pin2/TRF1 preferentially on the conserved Ser(219)-Gln site in vitro and in vivo (Kishi et al, 2001). Expression of Pin2 and its mutants has no detectable e ect on telomere length in transient transfection assays, however, a Pin2 mutant refractory to ATM phosphorylation on Ser(219) enhances cell killing by IR in A-T cells.…”
Section: Atm De®ciency In¯uences Telomere Chromatin Structurementioning
confidence: 99%
“…ATM phosphorylates multiple proteins involved in the DNA damage response, including p95/nibrin (Lim et al, 2000;Zhao et al, 2000), Brca1 (Cortez et al, 1999), the p53 tumor-suppressor gene (Banin et al, 1998;Canman et al, 1998), the checkpoint kinase chk2 (Blasina et al, 1999;Matsuoka et al, 2000), SMC1 (Banin et al, 1998;Kim et al, 2002;Yazdi et al, 2002), BLM (Beamish et al, 2002), FANCD2 (Taniguchi et al, 2002), and Pin2/Trf1 (Kishi et al, 2001). The phosphorylation of these proteins by ATM can regulate their functional activity.…”
Section: Introductionmentioning
confidence: 99%
“…20 Following DNA damage, ATM phosphorylates TRF1 and suppresses its ability to induce abortive mitosis and apoptosis. 21,22 On the other hand, TRF2 overexpression also negatively regulates telomere length, probably by an active degradation process. 19,23 TRF2 protects telomeres from end-toend fusion, 24 presumably because it mediates the proper folding of the telomere.…”
Section: Introductionmentioning
confidence: 99%